The everything psychology book : an introductory guide to the science of human behavior - Cherry, Kendra (Avon, Mass. : Adams Media, 2010)
There's nothing more fascinating-- or frightening-- than the ins and outs of the human mind. With this comprehensive guide, you'll achieve a better understanding of yourself-- and everyone else around you, too!
Psychology--yesterday and today -- How psychologists know what they know -- The biology of psychology -- Brain and mind--what makes us human -- How you experience your world -- Altered states of consciousness -- Conditioning and learning -- How you remember, why you forget -- Thinking, language, and intelligence -- Motives--why you do the things you do -- Emotions--feeling up, feeling down -- Human development--conception, infancy, and childhood -- Human development--adolescence -- Human development--adulthood and aging -- Personality and personality tests -- Social cognition--thinking about yourself and others -- Social interactions and interpersonal behavior -- Stress, coping, and health -- Disorders--when thinking and emotionality go awry -- Psychotherapy and other approaches to treatment -- Careers in psychology -- A glossary of psychological terms.
Includes bibliographical references (p. 276-277) and index.
Keywords: Psychology